Prosocial Behavior In The Dayak Ethnicity In Central Kalimantan Province - Revaldi, Muhammad; Faridah, Siti; Musfichin, Musfichin (Winter Journal: IMWI Student Research Journal, 2024)
Every behavior carried out by individuals is goal-oriented. This means that a behavior is always driven by the desire to achieve a goal, even though sometimes the individual does not know the specific goal. This also applies to prosocial behavior which can mean a heroic act to help others. Prosocial behavior arises through complex interactions between internal and external factors such as gender roles, social environmental conditions, age, and cultural norms and values that exist within a group (ethnicity). However, identifying prosocial behavior through ethnic factors is generally rare, especially among Dayak ethnic groups. This research aims to determine the level of prosocial behavior among Dayak ethnic groups in Central Kalimantan Province. The research method used is descriptive quantitative. The sampling technique uses a quota sampling approach with the criteria, Dayak ethnic community, aged in the age group 12-19 years, 20-29 years, 30-64 years, and ?65 years and domiciled in the Central Kalimantan area. So a sample of 150 people was found. The research results found that the level of prosocial behavior in the Dayak ethnic category was 56%, followed by the medium category with 44%. Meanwhile, for the low category, there is none. This shows that prosocial behavior among Dayak ethnic groups in Central Kalimantan Province is relatively high.